Seismic performance of a new through rib stiffener beam connection to concrete-filled steel tubular columns: An experimental study. (15th January 2017) - Zeinizadeh Jeddi, Mahdi; Ramli Sulong, N.H.; Arabnejad Khanouki, M.M.
Highlights: A through rib stiffener beam connection in CFT circular column is proposed. Exhibit a large hysteretic enclosed area, good ductility and excellent energy dissipation. Connection satisfies the seismic provisions and ductility design requirements for moment-resisting frames. Abstract: This paper proposes a new moment-resisting connection known as a through rib stiffener beam connection, which is directly passed through a pre-slotted circular column with concrete infill. Four half-scale cruciform specimens with orthogonal beams were tested under cyclic loading. The failure modes, hysteretic performance, rotation capacity, strength and stiffness degradation, ductility, and energy dissipation of the connections were analysed. The effect of different parameters, such as through rib stiffener and beam section size, on the connection performance was investigated. The experimental results indicated that the new through rib stiffener beam connected with circular columns exhibited a large hysteretic enclosed area, good ductility, and excellent energy dissipation. The results proved that the proposed connection satisfies the seismic provisions and ductility design requirements for it to be utilized as moment-resisting frames in a seismically active area.